Organoaxial gastric volvulus: a rare cause of an acute abdomen - Bauer, Katrin (GMS Interdiscip Plast Reconstr Surg DGPW, 2019)
We report the case of a 65-year-old male patient with massive epigastric pain of sudden onset and vomiting due to an organoaxial volvulus of the stomach. We comment on the surgical management in our case and discuss etiology and therapeutic options of this rare entity.